Rola referendum w powstawaniu państw po 1989 r. w Europie - Podolak, Małgorzata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The institution of the referendum is one of the forms of direct democracy. Referendums are understood as direct suffrage on important matters of state, or a part of its territory, that constitute the subject of the vote. In the processes of democratic transformation, outlooks on this institution of direct democracy evolve. Referendums have become a tool to express the will of the nation to choose in matters of sovereignty. This form of asking the nation has turned out to be effective for those communities with a strong sense of national identity and the belief that it is necessary for the state to be revived as a sovereign entity. The results of the referenda held in the Baltic states, in the Balkans and Ukraine have confirmed their peoples’ wills to independently exist within the framework of a sovereign state.